МОНАСТИРІ ПОЛТАВСЬКОЇ ЄПАРХІЇ (ЗА МАТЕРІАЛАМИ ЧАСОПИСУ ìПОЛТАВСКИЕ ЕПАРХИАЛЬНЫЕ ВЕДОМОСТИî) (Zaporizhzhia Historical Review, 2021)
In the article the analysis of organization structure of the orthodox monasteries in the Poltavskaya diocese is made on the base of the official church periodicals; their activity trends are characterized; the problems of the monasteries functioning since the 17th till the beginning of the 20th century are determined.